La part mystérieuse de Gregory Crewdson : dévoilement et construction de l’image photographique - Thomas, Cyril (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
Abstract The article outlines the career of Gregory Crewdson on the occasion of his retrospective at the Fotomuseum in Winterthur. Through an analysis of six photographic series, the author attempts to unravel the mysteries of Crewdson's images by understanding the hybrid form of his compositions between reality and surrealism, how he constructs his images, and how he implements a particular narrative from series to series.